Fresno County Bar Association's 18th Annual Judges Dinner at Crossland's Barn - Watkins, Howard::::::::: (1987)
Pamela Stone, Fresno County Bar Association President Howard Watkins and Fresno County Bar Association Vice-President Herbert Levy, Donald Fischbach